Comparison of Large and Small-Bore Chest Tubes in the Management of Malignant Pleural Effusion: A Prospective Cohort Study: Comparison of Large and Small-Bore Chest Tubes in the Management of Malignant Pleural Effusion - Younas, Muhammad; Anwar, Rukhsana; Ullah, Amjad; Rehman, Karishma; Saeed, Rabia; Sajjad, Sheema; Yaseen, Ambreen; Ashraf, Saadia (Pakistan Journal of Health Sciences, 2025)
Malignant pleural effusion (MPE) is a common complication in advanced cancers, often requiring chest tube drainage for symptom relief. Both small- and large-bore chest tubes are used, but their comparative effectiveness and patient comfort remain debated. Objectives: To compare clinical outcomes and complications of small versus large-bore chest tubes in MPE management. Methods: A prospective cohort study included 60 patients with MPE, divided into small-bore (Group A, n=30) and large-bore (Group B, n=30) groups. Outcomes measured were pain scores and duration of tube placement; complications included bleeding, wound infection, and subcutaneous emphysema. Data were analyzed using SPSS version 25.0. Results: Small-bore tubes were associated with significantly lower pain scores at 24 hours in patients ≤45 years (1.43 ± 2.15 vs 4.00 ± 1.67, p=0.037) and >45 years (1.17 ± 1.47 vs 2.92 ± 1.77, p=0.001). Pain reduction was consistent across genders and urban/rural groups. However, the duration of drainage was longer with small-bore tubes, particularly in patients >45 years (12.87 ± 3.07 vs 9.00 ± 2.80 days, p<0.001) and in rural patients (13.72 ± 2.96 vs 8.07 ± 2.54 days, p=0.0001). Complication rates, including bleeding, subcutaneous emphysema, and wound infection, were similar between groups (p>0.05). Conclusion: Small-bore chest tubes provide significantly lower pain while maintaining comparable safety to large-bore tubes. Despite a longer drainage duration, they represent a more comfortable and equally safe option for managing MPE.